Les origines de l’insécurité dans la région de l’Extrême-Nord du Cameroun entre la faillite de l’Etat et les fragilités sociales - Armel Dourmaïssou (Revue Hybrides)
The objective of this article is to analyze the origins of insecurity in the Far North region of Cameroon. Based on documentary research, direct observation and semi-structured interviews, this study reached the conclusion that insecurity in Cameroon and particularly in the Far North region is not without origins. It is the result of a tangle of political, social, economic, cultural and religious factors. Indeed, the phenomena of banditry, crime and terrorism in this region draw their main sources from certain major factors including the decision-making laxity of public authorities, security disparities, ambient poverty, globalization, rural exodus, radical religious tendencies. These result in the permanent vulnerability of populations to the risks of recruitment, deterioration and social breakdown.